Assessment of multifocality and axillary nodal involvement in early-stage breast cancer patients using 18F-FDG PET/CT compared to contrast-enhanced and diffusion-weighted magnetic resonance imaging and sentinel node biopsy - ERGÜL, Nurhan; Kadioglu, HÜSEYİN; KADIOĞLU, HÜSEYİN; Yildiz, Seyma; YILDIZ, ŞEYMA; YUCEL, Serap Baskaya; Gucin, ZÜHAL; GÜCİN, ZÜHAL; Erdogan, EZGİ BAŞAK; ERDOĞAN, EZGİ BAŞAK; Aydin, MEHMET; AYDIN, MEHMET; et al. (My University, 2015)
Background: Non-invasive evaluation of the extent of axillary nodal involvement in early-stage breast cancer (ESBC) patients and accurate assessment of multifocality are both challenging. Few reports have explored whether 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) might be more useful than other diagnostic methods in these contexts.